2011
DOI: 10.1111/j.1574-6976.2010.00250.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny, genomics, and symbiosis ofPhotobacterium

Abstract: Photobacterium comprises several species in Vibrionaceae, a large family of Gram-negative, facultatively aerobic, bacteria that commonly associate with marine animals. Members of the genus are widely distributed in the marine environment and occur in seawater, surfaces, and intestines of marine animals, marine sediments and saline lake water, and light organs of fish. Seven Photobacterium species are luminous via the activity of the lux genes, luxCDABEG. Much recent progress has been made on the phylogeny, gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
139
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(161 citation statements)
references
References 116 publications
(221 reference statements)
9
139
0
1
Order By: Relevance
“…This conclusion is analogous to that drawn at the species level for light-organ symbionts in the genus Photobacterium and their fish hosts (Dunlap et al, 2007;Urbanczyk et al, 2011), wherein more than one symbiont species is harbored. Thus, symbiont specificity can express itself at a number of phylogenetic levels among different bioluminescent symbioses; that is, while some host species will harbor more than one bacterial species (Fidopiastis et al, 1998), other hosts (for example, E. scolopes) are strongly species-specific, yet recognize many different strains as potential symbionts.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…This conclusion is analogous to that drawn at the species level for light-organ symbionts in the genus Photobacterium and their fish hosts (Dunlap et al, 2007;Urbanczyk et al, 2011), wherein more than one symbiont species is harbored. Thus, symbiont specificity can express itself at a number of phylogenetic levels among different bioluminescent symbioses; that is, while some host species will harbor more than one bacterial species (Fidopiastis et al, 1998), other hosts (for example, E. scolopes) are strongly species-specific, yet recognize many different strains as potential symbionts.…”
Section: Discussionsupporting
confidence: 53%
“…In the future, it will be informative to extend the investigation of both the symbiotic behavior and the genome content of the 12 E. scolopes-derived strains to those of other V. fischeri isolates that either are not light-organ symbionts or are specific to other squid or fish species (Nishiguchi et al, 1998;Urbanczyk et al, 2011). Because, over time, the host can sanction specific members of the symbiont population (Koch et al, 2014); it is critical to include the role of the host in the dynamics of the symbiont population (McFall-Ngai et al, 2010;Palmer et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…RDP Classifier analysis of 16S rRNA (19) indicated that the strain belongs to the genus Photobacterium. Similar to other characterized bioluminescent Photobacterium strains (20), the luminescence genes (luxA to -G) are arranged in an operon and are flanked by genes encoding the riboflavin biosynthesis machinery (rib genes) and by the lumPQ operon, which encodes the lumazine protein and a predicted regulator (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…However, this packaging allows the growth of CO 2 -resistant bacteria, including Gram-positive lactic acid bacteria and the Gram-negative bacterium Photobacterium phosphoreum (2-4). The latter has been identified as the specific spoilage organism (SSO) responsible for trimethylamine production and sensory spoilage of MAP cod (5, 6) and as the main spoilage bacterial species of several chilled marine fish, including cod, garfish, halibut, saithe, salmon, and shrimp (7-15).Multilocus analysis, based on 16S rRNA and gyrB and luxABFE genes, divided strains originally isolated and identified as P. phosphoreum into three distinct clades of P. phosphoreum, Photobacterium iliopiscarium, and Photobacterium kishitanii (16,17). The members of the P. phosphoreum species group have been reported as important for spoilage of raw MAP fish, and they include both luminous and nonluminous variants (5, 18).…”
mentioning
confidence: 99%